QUALITY CONTROL II: STATISTICAL PROCESS CONTROL AND RELIABILITY - Md. Fauzi Ahmad (Penerbit UTHM, 2023)
Welcome to the world of Quality Control - a journey into the heart of ensuring excellence in products and processes. This book delves into the fundamental principles, methodologies, and best practices that drive the pursuit of unparalleled quality across industries. Quality control is not just a process; it is a mindset that embodies the relentless pursuit of perfection. In today’s competitive landscape. delivering high-quality products and services is no longer an option; it is a necessity. This book is designed to equip readers with a comprehensive understanding of quality control principles and how they can be applied to drive continuous improvement and achieve customer satisfaction. The primary aim of this book is to provide a valuable resource for students, professionals, and quality enthusiasts alike, seeking to deepen their knowledge and expertise in the realm of quality control. I hope this book inspires you to embrace the spirit of continuous improvement, to strive for excellence in all your endeavors, and to embrace the transformative power of quality control. Remember, quality control is not just a practice; it is a commitment to excellence - a commitment we make to ourselves, our customers, and the world at large.